The Effect of Social Norms and Perceived Justice Through Personal Norms and Government Trust on Voluntary Tax Compliance With Patriotism and Tax Morale as Moderating Variables - MARFIANA, Andri; WIDYASTUTI, Tri; DARMANSYAH, Darmansyah (Journal of Governance, Taxation and Auditing, 2025)
Voluntary tax compliance serves as a fundamental pillar in supporting fiscal sustainability and national development. However, the suboptimal level of compliance indicates the presence of non-technical determinants that have not been fully identified. This dissertation aims to analyze the influence of social norms, personal norms, perceptions of fairness, and trust in government on voluntary tax compliance, while also considering the moderating roles of patriotism and tax morale. This study integrates the Theory of Planned Behavior (TPB) and the Slippery Slope Framework (SSF) to construct a behavioral model of compliance based on values and authoritative relations. Data were collected from 211 individual non-employee taxpayers in the Greater Jakarta area (Jabodetabek) using a quantitative approach with Structural Equation Modeling–Partial Least Squares (SEM-PLS). Additionally, the analysis was strengthened by qualitative data obtained from open-ended questions, which were processed using NVivo. The results indicate that all main variables significantly influence voluntary tax compliance. Tax morale was found to moderate the relationships between norms, trust, and tax compliance, whereas patriotism did not exhibit a significant moderating effect. The qualitative findings support the quantitative results, particularly regarding issues of perceived unfairness and low public trust due to corruption and a lack of fiscal transparency. This study makes a theoretical contribution by expanding value- and social-based compliance models and provides practical recommendations for the formulation of fairer, more inclusive, and trust-based tax policies.